(untitled) (Journal of the College of Basic Education, 2023)
An experiment was carried out in the wooden canopy at the University of Baghdad - College of Agriculture - Abu DhabiGharib - Department of Soil Sciences and Water Resources to study the response of the bean crop to rockPhosphate and agricultural sulfur and choosing the best combination between phosphate rock and sulfurAgricultural crop growth. Phosphate rock was added at levels (0, 1000 and 2000).kg m. e ’and agricultural sulfur (0, 1500 and 3000) kg 5. e ’at the end of the seasonPlant height, number of branches per plant, number of seeds per pod and seed yield were calculatedfor one plant and the dry matter weight of the vegetative part. The results showed: the rock increasedPhosphate was significantly increased in plant height, number of branches, number and yield of seeds, and material weightdryness of the vegetative part and the level of 2000 kg m.ha "is the best as the effect of additionAgricultural sulfur significantly increased the above-mentioned traits, and the level was 3000 kg K"e" is the best; as for the effect of the overlap between them, the level was (2000 kg m.ha.w0 kg 5 .H ’) is the best in all qualities as it gave the highest yield and the highest number ofBranches, seeds and dry matter 0 We conclude from this study the possibility of using phosphate rockInstead of manufactured phosphate fertilizers that are expensive because they are cheaper and available in IraqIt is a primary raw material for phosphate fertilizers.